Aspiration in Children and Adolescents with Neurogenic Dysphagia: Comparison of Clinical Judgment and Fiberoptic Endoscopic Evaluation of Swallowing - Beer, Sabrina; Hartlieb, Till; Müller, Arnd; Granel, Michael; Staudt, Martin (Neuropediatrics, 2014)
A total of 30 children and adolescents with dysphagia due to various chronic neurological disorders were assessed for their risk of aspiration. This assessment was performed clinically by experienced speech and swallowing therapists, and verified thereafter by fiberoptic endoscopy. We found the clinical judgment to be correct in only 70% (for aspiration of saliva), 55% (of puree), and 67% (of thin liquids). We conclude that, because of this unacceptably high error rate of clinical assessment, a fiberoptic evaluation of swallowing is a necessary diagnostic step both for the planning of therapy and for the development of feeding strategies in children and adolescents with neurogenic dysphagia.
Keywords: dysphagia; aspiration; fiberoptic endoscopic evaluation of swallowing